Cost-effectiveness of the MitraClip device in German heart failure patients with secondary mitral regurgitation - Bent Estler; Volker Rudolph; Yana Seleznova; Arim Shukri; Stephanie Stock; Dirk Müller (The European Journal of Health Economics, 2022)
Aim: To evaluate the cost-effectiveness of the MitraClip device (MitraClip) in addition to optimal medical therapy (OMT) in patients with heart failure and secondary mitral regurgitation in Germany. Methods and results A model-based economic evaluation was performed to estimate the incremental cost per quality-adjusted life-years (QALYs) for patients with a moderate-to-severe or severe secondary mitral regurgitation receiving MitraClip plus OMT compared with OMT alone from the statutory health insurance (SHI) perspective. Transition probabilities, data on survival rates, and hospitalization rates were obtained from the COAPT trial, a randomized-controlled multicenter trial. Data on health utility and costs were taken from published evidence. To assess parameter uncertainty, several deterministic and probabilistic sensitivity analyses were performed. The incremental costs per QALY gained were exteuro~59,728 (costs/incremental life years gained: exteuro~42,360). The results were most sensitive to the transition probabilities and the hospitalization rates. The probabilistic sensitivity analysis showed that the MitraClip strategy was cost-effective with a probability of 80% at a willingness-to-pay threshold of exteuro~67,000/QALY. Conclusions Depending on the willingness-to-pay threshold, for patients with heart failure and a moderate-to-severe or severe secondary mitral regurgitation the MitraClip can be cost-effective from the perspective of the German SHI. Graphical abstract
Keywords: 610; Heart failure; Secondary mitral regurgitation; Cost-effectiveness; Transcatheter-valve repair; MitraClip; Germany